The application of ivabradine in the management of ischaemic heart disease - Gurevich M.A.; Kuzmenko N.A. (Системные гипертензии, 2016)
Ischemic heart disease is not only serious disorder with special clinical characteristics and generally requiring multidisciplinary approach, but also a social and economic problem now. Heart rate control is one of the main therapeutic principles that should be applied in patients with ischemic heart disease. In practice there are always cases when b-blockers for reducing heart rate should not be used because of contraindications in patients (for example, disorders of carbohydrate and lipid metabolism). Ivabradine can be an alternative in this situation due to selective and specific inhibition of the If-channels current across the cardiac pacemaker, characterized by negative chronotropism without negative inotropic effect and without affecting atrioventricular conduction and blood pressure. Ivabradine therapy is generally well tolerated and increases adherence commitment of patients to treatment. Raenom® (Gedeon Richter, Hungary) is generic ivabradine of good-quality.